Nimitz at war : command leadership from Pearl Harbor to Tokyo Bay - Symonds, Craig L. (Oxford University Press, 2022)
Only days after the Japanese attacked Pearl Harbor, President Roosevelt tapped Chester W. Nimitz to assume command of the Pacific Fleet. From the early years of the war to the surrender ceremony on Tokyo Bay four years later, Nimitz carried the expectations of a nation impatient for revenge-- and transformed the devastated Pacific fleet into the most powerful and commanding naval force in history. Symonds covers all the major campaigns, and captures Nimitz's uncanny sense of when to assert authority and when to pull back. -- adapted from jacket